The Influence of Islamic Religiosity and Banjar Cultural Determinism on the Resilience and Entrepreneurial Character of MSME Entrepreneurs in South Kalimantan - Rusdiana Rusdiana; Zulfa Jamalie (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the influence of Islamic religiosity and Banjar cultural determinism on the resilience and entrepreneurial character of Micro, Small, and Medium Enterprise (MSME) entrepreneurs in South Kalimantan. The research is grounded in the assumption that entrepreneurial success is not solely determined by economic and managerial factors, but is also strongly influenced by spiritual values and local cultural traditions. Islamic religiosity functions as a moral and psychological foundation that shapes ethical business behavior, while Banjar cultural values such as kayuh baimbai strengthen social solidarity, cooperation, and collective resilience among entrepreneurs. This study employs a qualitative approach using the Library Research method. Data were collected from scientific journals, books, dissertations, theses, and relevant academic documents discussing Islamic entrepreneurship, Banjar culture, MSME resilience, and entrepreneurial character. The collected data were analyzed through content analysis to identify conceptual patterns and relationships among variables. The findings reveal that Islamic religiosity significantly contributes to the development of entrepreneurial resilience through values such as patience, sincerity, honesty, trustworthiness, and reliance on God (tawakal). Meanwhile, Banjar cultural determinism strengthens entrepreneurial character through collective values, mutual cooperation, social harmony, and adaptive work ethics. The interaction between religiosity and local culture creates resilient, ethical, and socially responsible entrepreneurial behavior among MSME actors in South Kalimantan. The novelty of this research lies in its integrative approach that combines Islamic religiosity and Banjar cultural determinism as interconnected variables in shaping entrepreneurial resilience and character. This study also contributes to the development of Islamic entrepreneurship studies by emphasizing the importance of local cultural values as socio-spiritual capital in strengthening MSME sustainability in Muslim communities